FEATURES OF PDL-1 EXPRESSION IN ABORTIVE TISSUES OF WOMEN WITH NON-DEVELOPING PREGNANCY ASSOCIATED WITH COVID-19 INFECTION - Shukurov, F.I.; Ruzmetova, N.F.; Ismoilova, Sh.I. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. Coronavirus infection significantly impacts the immune system, contributing to the development of inflammatory reactions that may disrupt normal implantation and embryo development. Aim. To study the level of Pdl-1 receptor expression in abortive tissues from non-developing pregnancies associated with COVID-19 and to evaluate the correlation between Pdl-1 expression and the clinical course of the infection. Materials and methods. The study included 60 women with non-developing pregnancies associated with COVID-19 infection. Participants were divided into two groups: Group I consisted of 30 women with pregnancies of 5-7 weeks, terminated by vacuum aspiration; Group II included 30 women with pregnancies of 8-12 weeks, terminated by medical abortion. The control group comprised 30 women who terminated pregnancies of 6-12 weeks by choice. Results. The results of IHC analysis of abortive tissues in Group I showed focal Pdl-1 receptor expression in decidual tissue in 67% of cases, heterogeneous expression in chorionic villi in 58% of patients, and diffuse expression in syncytiotrophoblast in 54% of cases. In Group II, moderate Pdl-1 receptor expression in decidual tissue was found in 57% of samples. Focal expression in syncytiotrophoblast was observed in 53% of cases, and heterogeneous expression in chorionic villi was detected in 51% of cases. In the control group, Pdl-1 expression was significantly lower compared to both COVID-19 groups, indicating the virus’s impact on the immunohistochemical characteristics of the tissues. Conclusions. The study revealed a high level of Pdl-1 receptor expression in abortive tissues from both groups with non-developing pregnancies associated with COVID-19. This increased expression likely reflects the negative impact of SARS-CoV-2 on fetal tissues, possibly due to the virus entering and damaging these tissues. Additionally, a correlation was identified between the level of Pdl-1 receptor expression and the severity of COVID-19’s clinical course. Specifically, a weak positive correlation was found between Pdl-1 expression levels and severe COVID-19 (r=0.24) and mild COVID-19 (r=0.14). This suggests that the severity of COVID-19 infection may be associated with Pdl-1 receptor expression levels in abortive tissues, potentially indicating a direct link to the immune response.